Weapons : a pictorial history - Tunis, Edwin 1897-1973. (Cleveland : World Pub. Co., 1954)
Describes in text and pictures weapons used through the ages, from the stones of prehistoric man to the bombs of modern times.
Keywords: Weapons -- History -- Juvenile literature; Armor -- History -- Juvenile literature; Military weapons -- History -- Juvenile literature